Residu Pestisida Produk Sayuran Segar Di Kota Ambon - Gratiana N.C Tuhumury; J. Audrey Leatemia; Ria Y Rumthe; Jeffie V Hasinu (Agrologia, 2012)
There are many methods to manage plant pests and diseases. One method that is always used by farmers is chemical control using synthetic pesticides. Utilization of synthetic pesticides inappropriately in terms of kind, target, dose/concentration, technique and time can be unsafe to the environment as well as the consumers. The objective of this research was to determine pesticide residues on fresh vegetables in the central market of Ambon city.  The vegetables being sampled were spinach (Amarantus indica), water cresant (Ipomoea aquatica), green mustard (Brassica juncea) and  long bean (Vigna sinensis) collected from Mardika and Passo local markets, Ambon City. Residue analysis was conducted at the Testing Laboratory of the Agricultural Post Harvest Research and Development Board of the Ministry of Agriculture, Bogor (Laboratorium Pengujian, Balai Besar Penelitian dan Pengembangan Pasca Panen Pertanian, Kementrian Pertanian, Bogor).  The results showed that the residues of Organochlorine (Chlorinated Hydrocarbons), Organophosphate, Carbamate and Pyrethroid were detected on sampled vegetables from central marketing at Ambon City. The residues of these classes of synthetic pesticides were detected in the form of Heptachlor, Aldrin, Endosulfan, Lindane, Chlorpyrifos, Profenofos, Diazinon, Monocrotophos, Parathion, Carbofuran, and Cypermethrin.  The residues detected were below Maximum Residue Limit (MRL) based on SKB of the Minister of Health and the Minister of Agriculture (Menteri Kesehatan dan Menteri Pertanian) No. 881/MENKES/SKB/VIII/1996 and No. 711/Kpts/TP270/8/96, and The Regulation of the Minister of Agriculture (Peraturan Menteri Pertanian) No.27/Permentan/ PP.340/5/2009